2008
DOI: 10.1111/j.1365-2788.2008.01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of problem behaviour during medication evaluations

Abstract: Background The focus of this review is on methods that are currently being used to evaluate the behavioural effects of medication for individuals with intellectual disabilities. First we describe what has been identified as the ideal criteria for conducting clinical trials and how these criteria may be adapted to do less controlled evaluations. The central theme is a review of the biological measures (e.g. labs, drug levels), behavioural rating scales and direct observation measures that are often used to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 102 publications
0
12
0
Order By: Relevance
“…Admittedly, there are several factors that might influence drug effectiveness such as genetic mutations or polymorphisms in genes that code for enzymes that metabolize drugs. 36 With the advancement of technology, increasingly larger numbers of studies have identified several possible polymorphisms that influence the development of autism [for reviews see: [37][38] ] and it is impossible to know which of these might influence other issues associated with the disorder beyond the core symptoms. We suggest that all pharmacological investigations clearly identify patients with GI symptoms prior to clinical trials.…”
Section: Should Clinical Trial Research Of Psychotropic Medication Inmentioning
confidence: 99%
“…Admittedly, there are several factors that might influence drug effectiveness such as genetic mutations or polymorphisms in genes that code for enzymes that metabolize drugs. 36 With the advancement of technology, increasingly larger numbers of studies have identified several possible polymorphisms that influence the development of autism [for reviews see: [37][38] ] and it is impossible to know which of these might influence other issues associated with the disorder beyond the core symptoms. We suggest that all pharmacological investigations clearly identify patients with GI symptoms prior to clinical trials.…”
Section: Should Clinical Trial Research Of Psychotropic Medication Inmentioning
confidence: 99%
“…The play condition was used in order to set up a stable environmental condition under which the occurrence of free operant problem behavior and adaptive behavior could vary as a function of the effects of HBOT. A similar approach to utilizing functional analysis sessions for assessing drug effects has been described elsewhere in the literature (Crosland et al 2003;Zarcone et al 2004;Zarcone et al 2008).…”
Section: Baselinementioning
confidence: 99%
“…It has been suggested that investigators working in the field of intellectual disability have a predisposition for choosing psychopharmacological interventions over behavioral interventions [Zarcone et al, 2008]. This may be particularly true for a genetic disorder such as FXS, as opposed to a behaviorally defined disorder such as autism, simply because FXS is characterized as a ''medical'' condition.…”
Section: Pharmacological Approachesmentioning
confidence: 99%